High Measures of Pre-Chemoradiotherapy Platelet-to-Albumin Ratio Indicates Poor Prognosis in Locally Advanced Pancreatic Cancer Patients - Kucuk A; Topkan E; Selek U; Haksoyler V; Mertsoylu H; Besen AA; Pehlivan B (Dove Medical Press, 2022)
Ahmet Kucuk,1 Erkan Topkan,2 Ugur Selek,3,4 Veysel Haksoyler,5 Huseyin Mertsoylu,6 Ali Ayberk Besen,6 Berrin Pehlivan7 1Clinic of Radiation Oncology, Mersin Education and Research Hospital, Mersin, Turkey; 2Department of Radiation Oncology, Baskent University Medical Faculty, Adana, Turkey; 3Department of Radiation Oncology, Koc University School of Medicine, Istanbul, Turkey; 4Division of Radiation Oncology, The University of Texas MD Anderson Cancer Center, Houston, TX, USA; 5Clinics of Medical Oncology, Medline Hospital, Adana, Turkey; 6Department of Medical Oncology, Baskent University Medical Faculty, Adana, Turkey; 7Department of Radiation Oncology, Bahcesehir University, Istanbul, TurkeyCorrespondence: Erkan Topkan, Department of Radiation Oncology, Baskent University Medical Faculty, Adana, Turkey, Tel +90-533-7381069, Fax +90-322-3444452, Email docdretopkan@gmail.comPurpose: In a lack of similar research, we meant to retrospectively investigate the prognostic significance of pre-chemoradiotherapy (C-CRT) platelet-to-albumin ratio (PAR) on the survival results of locally advanced unresectable pancreatic adenocarcinoma (LAPC) patients.Patients and Methods: The present analysis included 139 LAPC patients who received C-CRT in total. The utility of pre-C-CRT cutoff(s) reshaping survival data was explored using receiver operating characteristic (ROC) curve analysis. The primary and secondary objectives were the associations between PAR levels and overall survival (OS) and progression-free survival (PFS) outcomes.Results: At a median follow-up of 15.7 months (95% CI: 11.6- 19.8), the overall cohort's median and 5-year OS rates were 14.4 months (95% CI: 11.8- 17) and 14.7%, respectively, while the corresponding PFS rates were 7.8 months (95% CI: 6.5- 9.1) and 11.2%. Because the ROC curve analysis found 4.9 as the optimal PAR cutoff for both OS and PFS [area under the curve (AUC): 75.4%; sensitivity: 72.4%; specificity: 70.3%], we divided the patients into two PAR cohorts: PAR< 4.9 (N=60) and PAR≥ 4.9 (N=79). Comparative analysis per PAR group exhibited significantly worse OS (11.2 vs 18.6 months, and 9.8% vs 20.9% at 5 years, P=0.003) and DFS (7 vs 14.3 months, and 7.6% vs 16.2% at 5 years, P=0.001) with PAR≥ 4.9 versus PAR< 4.9, respectively. In multivariate analysis, the N0 nodal status, CA 19- 9≤ 90 U/mL, and PAR< 4.9 were found to be independent predictors of improved OS and PFS.Conclusion: The pre-C-CRT high PAR (≥ 4.9) robustly and independently prognosticated significantly worse OS and PFS results in inoperable LAPC patients who underwent definitive C-CRT.Keywords: pancreas cancer, prognosis, platelet-to-albumin ratio, concurrent chemoradiotherapy, survival outcomes